2011
DOI: 10.1080/00288233.2011.563784
|View full text |Cite
|
Sign up to set email alerts
|

Does early pregnancy nutrition affect the performance of triplet-bearing ewes and their progeny to weaning?

Abstract: Triplet-bearing ewes were offered one of three pastoral-based nutritional regimens from day 21 to day 50 of pregnancy (P21 to P50): su3b-maintenance (SM), maintenance (M) or ad lib (AD). From P50 to term, ewes were managed with the aim of ensuring total liveweight increased with expected gravid uterus mass. AD ewes were heavier (PB0.05) and had greater (PB0.05) body condition scores than both SM and M ewes at P50, with the latter two treatments not differing (P ! 0.05). Ewe nutritional treatment had no effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A number of studies have examined the impact of ewe nutrition in pregnancy on foetal growth and lamb birthweight (see review Kenyon and Blair 2014) but few have examined impacts in triplets. Kenyon et al (2011b) reported that early pregnancy nutrition had no impact on triplet birth weight. While Fogarty et al (1992) reported minimal to no impacts of mid-pregnancy nutrition.…”
Section: Birth Weightmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies have examined the impact of ewe nutrition in pregnancy on foetal growth and lamb birthweight (see review Kenyon and Blair 2014) but few have examined impacts in triplets. Kenyon et al (2011b) reported that early pregnancy nutrition had no impact on triplet birth weight. While Fogarty et al (1992) reported minimal to no impacts of mid-pregnancy nutrition.…”
Section: Birth Weightmentioning
confidence: 99%
“…Kleeman et al (1993) reported pastoral feeding conditions during mid-pregnancy had no effect on triplet lamb survival. In addition, the results from a series of studies under ryegrass based feeding conditions in early-, mid-and/or late-pregnancy suggest that ewes can be offered a minimum of 2 cm (approximately 800 kg DM/ha), until approximately two weeks pre-lambing,, without negatively affecting lamb survival (Morris and Kenyon 2004;Corner et al 2008;Kenyon et al 2011aKenyon et al , 2011bKenyon et al , 2012Kenyon et al , 2013, as long as intake is not restricted post this point. Interestingly in one of their studies, unrestricted feeding in late pregnancy actually negatively affected triplet survival (Kenyon et al 2012).…”
Section: Lamb Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…been reported from improved nutritional regimens in early pregnancy if the ewes are subsequently adequately fed in late pregnancy (Kenyon et al 2011b). These results suggest multiple-bearing ewe intakes in early pregnancy can be controlled to save herbage for later in pregnancy, with minimal, if any, impact on animal performance.…”
Section: What Is the Potential In The Future?mentioning
confidence: 99%